Activities for the adaptation of prostheses carried out by technicians in orthoses and prostheses - Parrea, R.; Ortega, P. (Revista Mexicana de Ingenieria Biomedica, 1989)
We describe the main steps to achieve the adaptation of mathematics in the school for the technicians in the theory and the prosthesis that works within the national rehabilitation institute. We discussed the problematics and some guidelines for cooperation between these technicians and biomedical engineers are outlined.